(untitled) (Revista de Ensino em Artes, Moda e Design, 2025)
A native species of the Amazon, açaí (Euterpe oleracea Mart.) is one of the most consumed fruits in the northern region of Brazil. Its production chain is important due to its cultural and economic identity, as well as the health benefits that the consumption of the pulp provides. However, processing waste is responsible for environmental, social, and economic problems. Among the byproducts, the fiber from the açaí seed stands out. The article presents two scenarios and possibilities (cellulose sheets and nonwoven) for reusing the fiber through an experimental methodology, called Material Driven Design (MDD), in a context of research and experimentation with waste. As a result, this work provides the possibility of relating two distinct production processes but with common backgrounds, highlighting rich teaching and learning narratives. Fourier Transform Infrared Spectroscopy (FTIR) on the fibers identified the presence of absorption bands commonly found in alternative materials used in paper production. Scanning Electron Microscopy (SEM) allowed visualizing the microstructure of the developed materials, revealing how changes in the processes directly impact their structure and properties. Visual and tangible analysis is crucial to provide insights into the changes that occurred and why they occurred, linking the theory of scientific bibliography to laboratory practice.